Correlation and Path Analysis for Grain Yield and Its Components of Lowland Rice Grown under Coastland Agroecosystem - Aprillia, Rika; Prayoga, Gigih Ibnu; Mustikarini, Eries Dyah (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2025)
Growth traits and yield components of rice plants affect yield. The magnitude of this relationship is seen from the correlation value between characters, and the direct and indirect effects are seen from the cross-fingerprint value. The study aims to determine which characters have a correlation with rice plant yield and their direct and indirect effects. The study was conducted from July 2023 to February 2024. The research location was in the rice fields of SPA Hamlet, Rias Village, Toboali, South Bangka Regency. The study used an experimental method, with a Randomized Complete Block Design (RCBD). The study was divided into 4 experimental blocks. The treatments were 10 superior varieties consisting of 8 inbred varieties (Inpari 32 HDB, Inpari 33, Inpari 42 Agritan GSR, Inpari 49 Jembar, Ciherang, Siliwangi, Padjajaran Agritan, and Cakrabuana Agritan) and 2 hybrid varieties (Mapan P05 and Bridantara 8). Data analysis was using correlation analysis and path analysis with Excel and SPSS applications. The results of the correlation analysis showed that only leaf width correlated with grain dry weight. Leaf width, plant height and number of productive tillers had the highest direct influence on yield. Leaf width characters can be recommended as selection characters in rice breeding. Keywords: correlation, hybrid, path analysis, superior rice